2020
DOI: 10.1038/s41467-020-17752-x
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the role of crystal orientation of protective layers for stable zinc anode

Abstract: Rechargeable aqueous zinc-ion batteries are a promising candidate for next-generation energy storage devices. However, their practical application is limited by the severe safety issue caused by uncontrollable dendrite growth on zinc anodes. Here we develop faceted titanium dioxide with relatively low zinc affinity, which can restrict dendrite formation and homogenize zinc deposition when served as the protective layer on zinc anodes. The asprepared zinc anodes can be stripped and plated steadily for more than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
329
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 501 publications
(334 citation statements)
references
References 36 publications
4
329
1
Order By: Relevance
“…The orthogonal lattice fringes confirm that this image is representative of a 'top view' of the synthesized TiO2, whereby, the (001) facet is highly exposed on the top surface of the materials. [28][29][30] This aligns with the data retrieved from characterization of the TiO2 supports by Raman spectroscopy and XRD. Although the calcined catalysts, with different facets exposed, possess a similar size of supported nanoparticles (ca.…”
Section: Resultssupporting
confidence: 83%
“…The orthogonal lattice fringes confirm that this image is representative of a 'top view' of the synthesized TiO2, whereby, the (001) facet is highly exposed on the top surface of the materials. [28][29][30] This aligns with the data retrieved from characterization of the TiO2 supports by Raman spectroscopy and XRD. Although the calcined catalysts, with different facets exposed, possess a similar size of supported nanoparticles (ca.…”
Section: Resultssupporting
confidence: 83%
“…Impressively, such long cycle life is superior to those of many previously reported Zn anodes at the same current density (Figure 5e). [ 31,36,39,48–52 ]…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, several strategies have been devoted to suppressing dendrite growth and minimizing side reactions, including optimizing electrolyte composition, [ 12–24 ] adopting gel or solid electrolyte, [ 25–27 ] and coating multifunctional protective layers. [ 28–33 ] Metallic Zn anode is a hostless electrode that is dynamically deposited and stripped at the Zn‐electrolyte interfaces, eventually undergoing huge volume variation during repeated Zn deposition‐dissolution processes. [ 34 ] Compared with common planar configuration, constructing 3D conductive skeletons with large free space is a feasible approach to accommodate metallic Zn, which can reduce the local current density and minimize the volume variation of Zn deposits.…”
Section: Introductionmentioning
confidence: 99%
“…Zn deposition orientation was changed, as evidenced also in SEM images of Zn plating ( Figure S22). [35] To investigate further the efficacyo fa ntisolvent electrolytes,Zn/polyaniline (PANI) coin cells were assembled where the PA NI was synthesized on carbon-cloth through in situ polymerization. [36] SEM images showed that the PA NI, featuring astamen-like nanostructure,was uniformly distributed on the carbon-cloth ( Figure S23).…”
Section: Research Articlesmentioning
confidence: 99%